The Effect of Education, Number of Industries, and Economics Growth on the Open Unemployment Rate in Indonesia - Kustieni, Vivi; Wiwin Priana Primadha (Journal of Regional Economics and Development, 2026)
This study aims to examine the impact of Education, Number of Industries, and Economic Growth on the Open Unemployment Rate in Indonesia. The method applied is a quantitative approach by using secondary data from the Badan Pusat Statistik (BPS). The data obtained were then processed through multiple linear regression analysis with the help of SPSS version 25 software to evaluate the partial and simultaneous effects of each variable. The results of the study indicate that partially: (1) education has a significant and negative impact on the open unemployment rate; (2) the number of industries shows a significant and positive effect; while (3) economic growth has no effect on the open unemployment rate in Indonesia. Simultaneously, all of these variables together have a significant effect on the open unemployment rate in Indonesia. The findings of this study are expected to be used as a reference for the central government in designing policies that improve public welfare.